Hubungan Status Fisik (Asa) Dengan Waktu Pulih Sadar Pasien Dengan General Anestesi Pada Laparatomi Cholelithiasis Di Murni Teguh Memorial Hospital - Sihaloho, Ardika; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2025)
General anesthesia is a medical intervention that causes loss of sensation and consciousness to facilitate surgical procedures, followed by a recovery phase where the patient regains full consciousness. Hemodynamic instability and delayed recovery often occur in laparotomy patients under general anesthesia, which is influenced by several factors, one of which is the physical status condition classified by the American Society of Anesthesiologists (ASA). Patients with a higher ASA classification are at greater risk of experiencing delayed recovery due to decreased organ and metabolic response to anesthetic agents. This study aims to determine the relationship between physical status (ASA) and recovery time in patients undergoing cholelithiasis laparotomy under general anesthesia. This study is a quantitative study with a cross-sectional design conducted in the Operating Theater Room – 8 Murni Teguh Memorial Hospital. The sample consisted of 45 respondents using a purposive sampling technique. The instruments used were an ASA physical status observation sheet and an Aldrete Score to assess recovery time. Data analysis used the Chi-Square test. The results showed that patients with a low ASA classification experienced a faster recovery of consciousness compared to patients with a high ASA classification who experienced delayed recovery. Statistical analysis showed a significant relationship between physical status (ASA) and recovery time in patients undergoing cholelithiasis laparotomy under general anesthesia (p-value <0.05). This finding confirms that patients at high risk of ASA require closer perioperative assessment and monitoring to prevent delayed recovery and reduce postoperative complications.